MINUTA AKTA YANG DIKELUARKAN NOTARIS TANPA TANDA TANGAN PENGHADAP - Denty Tri Septiwani Daoed (CV. KAMPUS AKADEMIK PUBLISING, 2025)
According to Decision Number: 657/Pid.B/2015/PNKis, it is stated that a Notary issued a copy of a deed; however, the original deed (minuta akta) from which the copy was derived was incomplete and had not yet been signed by the appearing parties. This research aims to identify the indicators that may hold a notary accountable for the authentic deed they have prepared. This study is normative legal research and employs a statutory approach. The method of analysis used in this study is qualitative analysis.The research findings indicate that a notary may be held accountable for the content of an authentic deed if there is evidence of intentional misconduct or negligence in its preparation. Furthermore, the forms of liability that may be imposed on a notary concerning the deed they prepare can be civil, criminal, or administrative/ethical in nature.Based on this conclusion, it is recommended that notaries, in the process of preparing authentic deeds, adhere to principles of morality, ethics, and exercise due diligence, accuracy, objectivity, and good faith in complying with all applicable legal provisions.